Angioleiomyoma of the Sinonasal Tract: A Systematic Review of an Uncommon Clinicopathological Entity - Velletrani, Gianluca; Maurizi, Riccardo; De Padova, Alessandro; Di Girolamo, Stefano (International Archives of Otorhinolaryngology, 2023)
Introduction Angioleiomyoma is a rare neoplasm that represents ∼ 0.2 % of all head and neck benign tumors and ∼ 2% of total cases of tumors of the sinonasal tract. It was once considered a possible subtype of leiomyoma, but, in the 2020 World Health Organization (WHO) classification of soft tissue tumors, it is accepted as a singular entity.Objective To systematically review the existing literature on angioleiomyoma in the light of the new classification of soft tissue tumors.Data Synthesis The present study was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. A comprehensive search in the PubMed, Cochrane, Scopus, and Google Scholar databases was performed in January 2022. The search items included the following keywords: nasal angioleiomyoma OR sinonasal angioleiomyoma OR nasal vascular leiomyoma OR sinonasal vascular leiomyoma. A total of 87 patients were evaluated. He age of the patients in the studies ranged from 15 to 88 years (mean age at diagnosis: 55.6 years). The most common site of involvement was the nasal septum (28.4 %), followed by the inferior turbinate (22.5%). The most common symptom was nasal obstruction (66.7%), followed by epistaxis (47.1%). Surgical excision represented the main treatment, and there was recurrence of pathology in only 1 case (0.9%).Conclusion To our knowledge, only 87 cases of sinonasal-tract angioleiomyoma have been previously described. The results of the present review seem to confirm the rarity and the benign nature of this neoplasm, and they seem to confirm the necessity to improve the available data about sinonasal-tract angioleiomyoma.
Keywords: angioleiomyoma; sinonasal tract; vascular leiomyoma; angiomyoma; benign nasal tumor; nasal neoplasm